If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 6 = 3y + 11 Reorder the terms: 6 + 8y = 3y + 11 Reorder the terms: 6 + 8y = 11 + 3y Solving 6 + 8y = 11 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 6 + 8y + -3y = 11 + 3y + -3y Combine like terms: 8y + -3y = 5y 6 + 5y = 11 + 3y + -3y Combine like terms: 3y + -3y = 0 6 + 5y = 11 + 0 6 + 5y = 11 Add '-6' to each side of the equation. 6 + -6 + 5y = 11 + -6 Combine like terms: 6 + -6 = 0 0 + 5y = 11 + -6 5y = 11 + -6 Combine like terms: 11 + -6 = 5 5y = 5 Divide each side by '5'. y = 1 Simplifying y = 1
| 4*2-y=8 | | T=9/5m+18 | | 1x-20x-525=1986 | | 2/3x+10+2x-30=180 | | 3600-.08y=y | | 5/6(24x-42)-2/3(18-24x)=2-20 | | 2/3x+10+z+y+2x-30=360 | | -6+2y=10x | | 6x+24=3x+99 | | .8y=3600 | | 1/2*(x/x+1)-(3x+1)=2 | | 12xy^3-3xy^2=0 | | 32x^2-20x+3=0 | | y=1/4x+3 | | 100[0.09(m+9)]= | | 7x^2-7x+28=0 | | (-6-6-16)/(2) | | 7-2(x-5)=8-3(2x-7) | | xy+6=xy+4x | | x/1.3=2 | | x=12+12 | | (8b-5)/3=9 | | 12+12=x | | (-4x/x+7)-(8/x+7) | | 1.1x-4=0.8 | | k=0.777777777778 | | (3/x-3)-(5/x-2) | | 24-12x-3x+15=4-4x | | 5x+16=9x+1 | | 15z=-60 | | 8(x-4)=14(x+2) | | -3x-55=11x+125 |